IMPLEMENTASI POLA KOMUNIKASI KEPEMIMPINAN KEPALA MADRASAH DALAM PEMBINAAN KARAKTER RELIGIUS - Hamlan, Hamlan; Mustafa, Sanimbar; Anirah, Andi (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2024)
The purpose of this paper is to analyze the communication pattern of madrasah heads carrying out the duties and functions of leadership in fostering the religious character of students. Qualitative methods are used in examining the meaning of content with data reduction, display and verification analysis techniques. This paper produces a tweet; First, the Head of the Madrasah carries out leadership duties with a democratic, participatory, interactive and surgical communication pattern, second; The implementation of democratic, participatory, interactive and functional communication patterns of madrasah heads is effective in developing the religious character of students. Third; The religious character values developed in students are obedience to Islamic teachings, mutual respect, social concern, individual and collaborative learning motivational attitudes, and producing honest, creative, responsible and inclusive student behavior. Abstrak Tujuan tulisan ini untuk menganalisis pola komunikasi kepala madrasah melaksanakan tugas dan fungsi kepempinan dalam pembinaan karakter religius peserta didik. Metode kualitatif digunakan dalam menelaah makna kontent dengan teknik analisis reduksi, display dan verifikasi data. Tulisan ini menghasilkan tumuan; pertama, kepala madrasah melaksanakan tugas kepemimpinan dengan pola komunikasi demokratis, partisipatif, interaktif dan pskologis, kedua; implementasi pola komunikasi demokratis, partisipatif, interaktif dan pskologis kepala madrasah efektif mengembangkan karakter religius peserta didik. Ketiga; nilai-nilai karakter religius yang dikembangkan pada pribadi peserta didik adalah taat menjalankan ajaran Islam, saling menghormati, memiliki kepedulian sosial, memiliki sikap motivasi belajar individu dan kolaboratif, serta menghasilkan perilaku peserta didik yang jujur, kreatif, bertanggung jawab dan inklusif.